Religião, sexualidade e poder: a liderança religiosa e política dos evangélicos pentecostais - Silva, Maria Auxiliadora da (2009)
This research investigated the relationship between religion, sexuality and power in religious and political leadership of pentecostal Gospel. "Religion, Sexuality and Power - The religious and political leadership of pentecostal Gospel" proposes, in its first part, a theoretical reflection in which it discusses the articulation of sexuality, power and religion in the life of humans. Also discussed the relationship between religion and politics focusing on the group of Gospel in their participation in contemporary Brazilian policy. The second part is of field research taking as representatives of the group Pentecostal Church of the Gospel Square and the Universal Church of the Kingdom of God. The methodology used was the case study, having as interviewed eight leaders Pentecostal: four men and four women. The main techniques used in data collection were observations and semi-structured interviews. The data analysis revealed that the sexuality of leaders is controlled by the authorities that they exercise the powers of their roles in religious and political leadership. Verified a huge difference between the leaders in male and female aspects related to sexuality and power. However, in both sexes, the power makes the leader an object much more desired, even unattainable. In turn, as object wished, also wishes, but not may desire. This is the price to be paid involving direct religion, sexuality and power on the experience of each. Religion, power and sexuality are enmeshed forces that permeate the life and the quotidian of leaders and, by extension, the members and participants of pentecostal Churches. This research presents, therefore, as a contribution to studies on group Pentecostal with its significant growth and participation, increasingly, its leadership in politics